Sesamum Technology: A Crop Diversification Alternative in Punjab - Parminder Kaur and Narinderpal Singh (Indian Journal of Extension Education, 2018)
Sesamum can play an important role in crop diversification in specific locations. Due to its good demand inlocal market there is a need to raise the Sesamum production through increase in area and productivity. Topromote its new technology, Punjab Agricultural University, Ludhiana has conducted frontline demonstrationsin Punjab during Kharif, 2016 for testing and popularizing Sesamum variety in Punjab Til No.2. The studybased on 8 front-line demonstrations conducted in Amritsar district of Punjab reveals that the cultivation ofSesamum can be a viable alternative to paddy crop under scarce water resources in general and for smallfarmers, in particular, having lesser staying power to get assured irrigations. The sesamum variety recordedplant height (138.78 cm), no. of plants /m2 (52), no. of pods /plant (99.5), weight of 100 seeds (3.46 g), andno. of seeds/pod (100.5). The demonstrated technology recorded grain yield 5.50 q/ha which is 83.96 percent higher yield than local check variety. The benefit-cost (B:C) ratio of this technology was 1.01. Theinsect pest and diseases were in the range of 0.25 to 1.50 and 0.25 to 2.50 per cent respectively. Thetechnology gap, extension gap and technology index were 1.50 q ha-1, 2.55 q ha-1 and 21.42 per centrespectively. It was also observed that the productivity of Sesamum can be doubled with the help of availableadvanced technology.